Criminal Responsibility for the Crime of Genocide and the Penalties under National and International Law - Elias, Ziada; Al-Baaj, Alaa (Journal of Legal Sciences, 2026)
Genocide is considered one of the most serious international crimes, threatening global peace and security. Iraq witnessed horrific atrocities after 2014, particularly against the Yazidi community by ISIS, involving mass killings, slavery, rape, and forced displacement. This paper examines the penalties for the crime of genocide under Iraqi legislation compared to international law, highlighting legislative gaps and emphasizing the need to implement international norms to ensure justice for victims.